CONVERSATION AS A METHOD OF TEACHING DIALOGICAL SPEECH TO PRESCHOOL CHILDREN (Conferencea, 2022)
To solve the problem of the development of dialogic speech in senior preschool age, the joint activity of a preschooler with an adult is of great importance. In the process of it, the tasks of instructing, discussing, agreeing, evaluating actions arise. Contact is established and relationships are maintained, opinions and ideas are exchanged, mutual understanding arises, and activity is stimulated. At the same time, the main conditions for the development of dialogic speech are the initiative and activity of the child himself, which should be encouraged and encouraged in every possible way. It has been established that the influence of children's joint activity on dialogical speech increases significantly if they are shown that its success depends on the ability to communicate and negotiate. Joint activity contributes to children's awareness of the need to possess dialogic skills, and, consequently, develops them